Sistem Informasi Key Performance Indicator Penjualan Metode OMAX berbasis Web System Application - Giandari Maulani; Kharisma Nur Qhoirunnisa; Tri Mulyani (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
PT. Winn Appliance is a company engaged in the sale of household commodities, namely gas appliances. Currently in carrying out sales data reporting sales PT. Winn Appliance still uses Microsoft Excel and Whatsapp media as a medium for providing information and reports on sales results which will later serve as indicators for company management in determining the decision to extend the work contract. The goals of the company need to be achieved through a predetermined target for each sales, as well as measuring the achievement of these targets. Then these measurements can use a Key Performance Indicator which integrates with each other. For this reason, a Web System Application-based Key Performance Indicator information system was established. Then in determining the design requires an appropriate method and the method applied in this research is using the OMAX (Objective Matrix) method. The programming language uses the PHP Framework Code Igniter and MySql as a database storage regulator that can show the Sales Performance Indicator target value that has been achieved. The result of this research is Information System Key Performance Indicator Sales of OMAX method based on Web System Application which can facilitate the management of PT. Winn Appliance in monitoring sales and is useful for determining employment contract decisions.